Moving Object Detection, Tracking and Classification Using Optimized Multiple Perceptron Neural Network - Kumar, A; kaur, M (International Journal of Computer Sciences and Engineering, 2025)
Currently, the detection of moving objects is being mandatory in most of the security systems. Moving objects are crucial in the areas of image searching, automatic annotation and for the understanding of scenes. Although the detection is a challenging task therefore, the detection of moving objects is essential to describe the accurate position and unique features of an object. The tracking of moving objects used in most of the computer vision applications. The detection and identification of objects form a moving scene or a video is called tracking. Some of the major challenges are occurred because of the position of moving cameras are not stable hence. The visibility of pictures is affected and the shadow area also considered as a challenge for the detection. In the previous research, Decision tree (J48), MLPNN (Multi-Layer Perceptron Neural Network) and KNN (K- Nearest Neighbor) used for the detection of moving objects but all these approaches are supervised that are not applicable to easily classify the data. The accuracy decreased and the false error rates increased. To sort out the previous work challenges, the current approaches are considered as namely as Optimized-MLPNN that easily stables the position and fix the location of objects.. For the classification, filters are trained that performed well and used the basic three operators as selection, crossover and mutation for the classification of moving objects. In proposed work, improve the accuracy rate, specificity, precision and reduce the FAR, FPR and FRR rate using simulation Tool MATLAB 2016a.